Occupation in the East : the daily lives of German occupiers in Warsaw and Minsk, 1939-1944 - Lehnstaedt, Stephan 1980- (Berghahn Books, 2016)
Germans on duty in the East in Warsaw and Minsk -- Prescribed daily activities -- Transgression of norms -- The attitude of the "overlords" -- Violence in everyday life : the German occupiers and the local population